Outward FDI and a global compact on home-country investment incentives - Marta Soprana (Columbia University, Columbia Center on Sustainable Investment (CCSI), 2020)
An international framework for disciplining outward FDI incentives could help address the potentially distortive effects of certain home-country measures that governments are increasingly employing to promote or support outward FDI activities. This Perspective highlights which factors should be considered to increase the feasibility of undertaking such a global compact approach.
Keywords: 330